Study on pedestrian and cyclist interactions at signalised bicycle-cum-pedestrian crossings - Ng, Chermaine Xin Yi. (2013)
Cycling has been mainly regarded as a form of reaction in Singapore for many years, limited to bicycle towns, such as Pasir Ris and Tampines, and also parks. In recent years, the Singapore Government have been promoting cycling as a form of transport to and fro various transport nodes in Singapore. This leads to a rise in interest in cycling as forms of reaction, transportation and also exercise.